PEMBELAJARAN PENDIDIKAN AGAMA ISLAM INTERDISIPLIN DI SEKOLAH DASAR - Rusmawati Rusmawati; Nur Raafitta Suci Zahratun Nisa; Zahrotun Nisa (SITTAH: Journal of Primary Education, 2022)
Islamic Religious Education (PAI) is a subject that is always interesting to study because it is a compulsory subject at all levels of education and focuses on the alignment of intellectual, moral, and skill aspects of students at school. This paper aims to discuss the relevance of an interdisciplinary approach to learning Islamic Religious Education in Elementary Schools (SD). This study has used descriptive qualitative research in the form of library research. Excavation of library data focused on several concepts regarding interdisciplinary approaches, PAI learning, and similar concepts that are relevant. Analysis of the data using a content analysis model. This study found that interdisciplinary PAI learning is part of integrated learning. At the elementary school level, integrated learning is manifested in integrative thematic learning that combines competencies from several subjects as representatives of scientific disciplines into a network of specific themes. Its relevance becomes evident because the latest curriculum, the independent curriculum, does not erase it but instead enriches it with an open attitude to other relevant approaches.